Financing animal health services in some African countries - Anteneh, A. (International Livestock Centre for Africa, 1983)
Summary & conclusions of a paper on the financing of animal health services in 13 West & Central African countries, and Madagascar in the 1970s. Discusses the size & composition of animal health services operating budget, considering expenditures for animal health services & livestock's role in the economy, & sources & methods of financing. Includes some indicators of the adequacy of animal health services.